Olefin-based polymer composition and its use

JP7610403B2Active Publication Date: 2025-01-08MITSUI CHEMICALS INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020212578
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-22
Publication Date
2025-01-08
Estimated Expiration
2040-12-22

AI Technical Summary

Benefits of technology

【0016】 本発明によれば、摺動性を向上させるとともに、高温下での使用においても変形を抑制できるオレフィン系重合体組成物および該オレフィン系重合体組成物から得られる成形体が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610403000001
    Figure 0007610403000001
Patent Text Reader

Abstract

To provide an olefinic polymer composition having high slidability and excellent heat resistance.SOLUTION: The present invention relates to an olefinic polymer composition, comprising an ethylenic polymer composition (A), a propylenic polymer (B), inorganic filler (C), and a fatty amide (D). The ethylenic polymer composition (A) comprises: an ultrahigh molecular weight ethylenic polymer (component (a-1)) having an intrinsic viscosity [η] in a range of 10 to 40 dl / g as measured in a decalin solvent at 135°C; and a low molecular weight or high molecular weight ethylenic polymer (component (a-2)) having an intrinsic viscosity [η] in a range of 0.1 to 5 dl / g as measured in a decalin solvent at 135°C, where, when a total mass of the component (a-1) and the component (a-2) is taken as 100 mass%, the component (a-1) is in a range of 15 to 75 mass% and the component (a-2) is in a range of 85 to 25 mass%, has a density in a range of 930 to 980 kg / m3 and has an intrinsic viscosity [η] in a range of 5 to 35 dl / g as measured in a decalin solvent at 135°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an olefin polymer composition having excellent sliding properties and heat resistance, and uses thereof. [Background technology]

[0002] Ethylene polymers having an extremely high molecular weight, so-called ultra-high molecular weight ethylene polymers, are superior to general-purpose ethylene polymers in impact resistance, abrasion resistance, chemical resistance and strength, and have excellent characteristics as engineering plastics.

[0003] It is known that such ultra-high molecular weight ethylene polymers can be obtained by using known catalysts such as so-called Ziegler catalysts consisting of a halogen-containing transition metal compound and an organometallic compound, and magnesium compound-supported catalysts.

[0004] Due to the high molecular weight of ultra-high molecular weight ethylene polymers, it is difficult to perform melt molding, which is a general molding method for resins. The ram extrusion method is already a commonly used method for producing molded bodies of ultra-high molecular weight ethylene polymers (Patent Document 1).

[0005] Furthermore, as a method for improving the sliding properties, abrasion resistance, heat resistance, and rigidity of an olefin resin composition, it has been proposed to incorporate a particulate inorganic filler such as talc into the olefin resin composition (Patent Document 2). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 55-28896 [Patent Document 2] Japanese Patent Application Publication No. 01-272646 Summary of the Invention [Problem to be solved by the invention]

[0007] However, olefin-based polymers are inferior in heat resistance to other engineering plastics such as polyamide resins, polyacetal resins, polyester resins, polyphenylene sulfide resins, and polycarbonate resins. Therefore, there is a demand for compositions having improved heat resistance without impairing the inherent sliding properties and abrasion resistance of olefin-based polymers.

[0008] An object of the present invention is to provide an olefin polymer composition having excellent sliding properties and heat resistance. [Means for solving the problem]

[0009] As a result of intensive investigations, the present inventors have found that the above-mentioned problems can be solved by adding specific amounts of a propylene-based polymer, an inorganic filler, and a fatty acid amide to a specific ethylene-based polymer composition, and have thus completed the present invention.

[0010] The present invention relates to the following [1] to [8]. [1] An ethylene-based polymer composition (A), a propylene-based polymer (B), an inorganic filler (C) and a fatty acid amide (D), comprising an ultra-high molecular weight ethylene-based polymer (component (a-1)) having an intrinsic viscosity [η] of 10 to 40 dl / g as measured in decalin solvent at 135°C, and a low-molecular weight to high molecular weight ethylene-based polymer (component (a-2)) having an intrinsic viscosity [η] of 0.1 to 5 dl / g as measured in decalin solvent at 135°C, wherein the component (a-1) is in the range of 15 to 75 mass% and the component (a-2) is in the range of 85 to 25 mass%, and the density is 930 to 980 kg / m 3 and an intrinsic viscosity [η] measured in decalin solvent at 135° C. is in the range of 5 to 35 dl / g.

[0011] [2] The olefin polymer composition according to [1], wherein the propylene polymer (B) is a composition of a propylene homopolymer (b-1) and a propylene-α-olefin copolymer (b-2).

[0012] [3] The olefin polymer composition according to [1] or [2], wherein the content of the ethylene polymer composition (A) is 10 to 50 mass%, the content of the polypropylene (B) is 30 to 70 mass%, and the content of the inorganic filler (C) is in the range of 0.1 to 30 mass% (wherein the olefin polymer composition is 100 mass%).

[0013] [4] The olefin polymer composition according to any one of [1] to [3], further comprising a modified olefin polymer (E). [5] The olefin polymer composition according to [4], wherein the content of the modified olefin polymer (E) is in the range of 0.1 to 5 mass % (wherein the olefin polymer composition is taken as 100 mass %).

[0014] [6] The olefin polymer composition according to any one of [1] to [5], wherein the content of the fatty acid amide (D) is in the range of 0.1 to 15 mass % (wherein the olefin polymer composition is taken as 100 mass %).

[0015] [7] The olefin polymer composition according to any one of [1] to [6], wherein the inorganic filler (C) is a glass fiber. [8] A molded article obtained by injection molding the olefin polymer composition according to any one of [1] to [7]. Effect of the Invention

[0016] According to the present invention, there are provided an olefin polymer composition which has improved sliding properties and is capable of suppressing deformation even when used at high temperatures, and a molded article obtained from said olefin polymer composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] The present invention will be specifically described below. Ethylene-based polymer composition (A) The ethylene polymer composition (A), which is one of the components of the olefin polymer composition of the present invention, contains an ultra-high molecular weight ethylene polymer (component (a-1)) having an intrinsic viscosity [η] measured in decalin solvent at 135°C in the range of 10 to 40 dl / g, and a low- to high-molecular weight ethylene polymer (component (a-2)) having an intrinsic viscosity [η] measured in decalin solvent at 135°C in the range of 0.1 to 5 dl / g.

[0018] <Component (a-1)> The ultra-high molecular weight ethylene polymer (component (a-1)) constituting the ethylene polymer composition (A) according to the present invention preferably has an intrinsic viscosity [η] in the range of 10 to 35 dl / g, more preferably 12.5 to 35 dl / g.

[0019] By containing the component (a-1) having an intrinsic viscosity [η] within the above range, the resulting olefin polymer composition is excellent in self-lubrication, impact strength, chemical resistance, and the like. The component (a-1) according to the present invention is a homopolymer of ethylene or a copolymer of ethylene and an α-olefin such as propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 4-methyl-1-pentene, or 3-methyl-1-pentene. Of these, it is preferable to use a homopolymer of ethylene or a copolymer of ethylene and the above-mentioned α-olefin, which is composed mainly of ethylene, and it is particularly preferable to use a homopolymer of ethylene.

[0020] <Component (a-2)> The low to high molecular weight ethylene polymer (component (a-2)) constituting the ethylene polymer composition (A) according to the present invention preferably has an intrinsic viscosity [η] in the range of 0.3 to 3 dl / g, more preferably 0.5 to 2.5 dl / g.

[0021] By containing the component (a-2) having an intrinsic viscosity [η] within the above range, the resulting olefin polymer composition has good melt fluidity. The component (a-2) according to the present invention is a homopolymer of ethylene or a copolymer of ethylene and an α-olefin. The α-olefin constituting the copolymer is a linear or branched α-olefin having 3 to 20 carbon atoms, specifically, propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 3,4-dimethyl-1-pentene, 4-methyl-1-hexene, 3-ethyl-1-pentene, 3-ethyl-4-methyl-1-pentene, 3,4-dimethyl-1-hexene, 4-methyl-1-heptene, 3,4-dimethyl-1-heptene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene. Among these, ethylene homopolymers are preferably used from the viewpoint of the self-lubricating properties of the resulting olefin polymer and molded article.

[0022] In the ethylene polymer composition (A) according to the present invention, the total mass of the above components (a-1) and (a-2) is taken as 100 mass%, and the component (a-1) is in the range of 15 to 75 mass%, preferably 20 to 60 mass%, more preferably 25 to 50 mass%, and the component (a-2) is in the range of 85 to 25 mass%, preferably 80 to 40 mass%, more preferably 75 to 50 mass%.

[0023] An olefin polymer composition containing the ethylene polymer composition (A) in which the amounts of component (a-1) and component (a-2) contained in the ethylene polymer composition (A) satisfy the above ranges has excellent self-lubricity, impact strength, chemical resistance, etc.

[0024] The ethylene polymer composition (A) according to the present invention has a density of 930 to 980 kg / m 3 , preferably 940 to 975 kg / m 3 , more preferably 950 to 970 kg / m 3 is in the range.

[0025] An olefin polymer composition containing the ethylene polymer composition (A) having a density falling within the above range is excellent in self-lubrication, impact strength, chemical resistance, and the like. The density was measured in accordance with ASTM D1505.

[0026] The ethylene polymer composition (A) according to the present invention has an intrinsic viscosity [η] measured in decalin solvent at 135° C. in the range of 5 to 35 dl / g, preferably 10 to 30 dl / g, more preferably 15 to 25 dl / g. The olefin polymer composition containing the ethylene polymer composition (A) having an intrinsic viscosity [η] falling within the above range is excellent in self-lubrication, impact strength, chemical resistance, and the like.

[0027] <Production method of ethylene polymer composition (A)> The ethylene polymer composition (A) according to the present invention can be produced by mixing the previously obtained components (a-1) and (a-2) described above. As preferred embodiments, the following methods (M-1) and (M-2) can be exemplified.

[0028] (M-1) A method of producing the component (a-1) and the component (a-2) in advance in the presence of a known olefin polymerization catalyst, and then mixing or kneading the components. (M-2) A production method by a multi-stage polymerization method including at least two steps, namely, a first step of producing component (a-1) in the presence of a known olefin polymerization catalyst, and a second step of producing component (a-2).

[0029] In this case, the olefin such as ethylene used in the polymerization can be any of the various olefins described in the above items of component (a-1) and component (a-2) without any restrictions. Any known catalyst for olefin polymerization can be used without any particular limitation as long as it can produce the above-mentioned components (a-1) and (a-2).Specific examples include Ziegler-Natta catalysts made of titanium tetrachloride or titanium trichloride, solid titanium catalysts supported on a carrier such as magnesium, metallocene catalysts, and postmetallocene catalysts.

[0030] As the method for producing the ethylene polymer composition (A) according to the present invention, among the above-mentioned methods, the method of polymerization in multiple stages as shown in (M-2) is preferably used because it allows the component (a-1) to be finely dispersed in the component (a-2) to obtain a homogeneous ethylene polymer composition (A).

[0031] Furthermore, by post-polymerizing component (a-2) together with component (a-1), the compatibility between the ethylene-based polymer composition (A) and the propylene-based polymer (B) is improved, and as a result, the ethylene-based polymer composition (A) is uniformly dispersed or bonded, and an olefin-based polymer composition having an excellent balance of properties such as self-lubricity, impact strength, chemical resistance, appearance, and moldability, and particularly excellent self-lubricity and moldability, can be obtained. The multi-stage polymerization method can be carried out in the same manner as the polymerization method described in JP-A-1-129047, for example.

[0032] <Propylene polymer (B)> The propylene polymer (B), which is one of the components of the olefin polymer composition of the present invention, is a propylene homopolymer (b-1) or a copolymer of propylene with ethylene or an α-olefin having 4 or more carbon atoms, specifically, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 4-methyl-1-pentene or 3-methyl-1-pentene, etc., and is a propylene-α-olefin copolymer (b-2) having an α-olefin content of usually 50 mol % or less, preferably 40 mol % or less, more preferably 20 mol % or less.

[0033] The propylene polymer (B) according to the present invention is not particularly limited as long as the moldability of the olefin polymer composition containing the propylene polymer (B) is not impaired, but the melt flow rate (MFR) (ASTM D-1238, 230°C, load 2160 g) is usually in the range of 0.01 to 100 g / 10 min, preferably 0.1 to 80 g / 10 min.

[0034] The propylene polymer (B) according to the present invention is preferably a mixture (composition) of a propylene homopolymer (b-1) and a propylene / α-olefin copolymer (b-2). The mixture ratio of the propylene homopolymer (b-1) and the propylene / α-olefin copolymer (b-2) is particularly preferably in the range of 20 to 80% by mass for the propylene homopolymer (b-1) and 80 to 20% by mass for the propylene / α-olefin copolymer (b-2), when the total amount of (b-1) and (b-2) is taken as 100% by mass, from the viewpoint of heat resistance of the olefin polymer composition containing the propylene polymer (B).

[0035] <Inorganic filler (C)> The inorganic filler (C), which is one of the components of the olefin polymer composition of the present invention, is a known material used as a reinforcing material or filler for rubber, resin, etc., and specifically includes silicas such as dry process amorphous silica (aerosil), wet process amorphous silica (white carbon), crystalline silica (cristobalite, quartz), and diatomaceous earth; aluminas such as alumina (α-alumina), aluminum hydroxide, or alumina gel (gibbsite, boehmite); synthetic aluminum silicate (amorphous) and natural aluminum silicate (kaolin, calcined Examples of the inorganic filler (C) include aluminum silicates such as synthetic kaolin, natural magnesium silicate (talc), synthetic magnesium silicate, and synthetic basic magnesium silicate, natural or synthetic smectite clay minerals (bentonite, montmorillonite), synthetic aluminosilicates (zeolites), alkaline earth metal salts such as calcium carbonate, magnesium carbonate, and barium sulfate, powdery or granular materials such as magnesium oxide and magnesium hydroxide, and fibrous materials such as carbon fiber, alumina fiber, ceramic fiber, silica fiber, and glass fiber. Among these inorganic fillers (C), fibrous materials are preferred, and glass fiber is particularly preferred from the viewpoint of heat resistance.

[0036] <Glass fiber> The glass fiber according to the present invention is not particularly limited, and examples thereof include borosilicate glass, E glass, S glass, A glass, AR glass, C glass, D glass, T glass, NE glass, H glass, quartz, low dielectric constant glass, and high dielectric constant glass. Among these, D glass is preferred because glass fibers having a refractive index within the above range can be easily obtained. The glass fiber may be one type or two or more types.

[0037] The glass fiber according to the present invention may be a long fiber, a short fiber, or a chopped fiber, and the cross-sectional shape perpendicular to the longitudinal direction of the glass fiber is not particularly limited, but is preferably circular.

[0038] The glass fiber according to the present invention may be a fiber whose surface has been treated with a surface treatment agent such as a silane coupling agent, a titanate coupling agent, a boron coupling agent, an aluminate coupling agent, or a zircoaluminate coupling agent, or a conventionally known sizing agent.

[0039] The glass fiber according to the present invention has an average fiber diameter of preferably more than 6.5 μm and not more than 20 μm, more preferably 8 to 19 μm, and further preferably 10 to 18 μm. When glass fiber having an average fiber diameter within the above range is used, the fiber is unlikely to be broken when a molded article is formed from the olefin polymer composition of the present invention, and a molded article having excellent impact strength, appearance, rigidity, heat resistance, etc. can be easily formed.

[0040] The glass fiber according to the present invention has an average fiber length of preferably 0.1 to 15 mm, more preferably 0.3 to 13 mm, and further preferably 0.5 to 13 mm. When the glass fiber having an average fiber length within the above range is used, the reinforcing effect of the glass fiber on mechanical properties is easily exhibited, and a composition having excellent dispersibility can be easily obtained, which is preferable. The average fiber diameter and the average fiber length of the glass fibers are values ​​calculated by visually measuring the lengths of 100 glass fibers using an optical microscope.

[0041] Fatty acid amide (D) The fatty acid amide (D), which is one of the components of the olefin polymer composition of the present invention, is usually a fatty acid amide having 12 or more carbon atoms. Specific examples thereof include saturated fatty acid amides such as lauric acid amide, palmitic acid amide, stearic acid amide, and behenic acid amide; unsaturated fatty acid amides such as erucic acid amide, oleic acid amide, brassidic acid amide, and elaidic acid amide; fatty acid bisamides such as methylene bisstearic acid amide, ethylene bisstearic acid amide, and ethylene bisoleic acid amide; and saturated or unsaturated fatty acid alkylamides such as fatty acid methylamide and fatty acid ethylamide. Among these fatty acid amides, erucic acid amide is particularly preferred from the viewpoint of sliding properties.

[0042] Modified olefin polymer (E) The modified olefin polymer (E), which is one of the components of the olefin polymer composition of the present invention, is a polymer that contains an olefin-derived structural unit as a main component and a structural unit having a functional group containing a heteroatom (hereinafter, also simply referred to as a "functional group") in a proportion of preferably 0.1 to 10 mass%, more preferably 0.5 to 5 mass%. This proportion can be determined, for example, by the method described in

[0067] to

[0071] of WO 2015 / 011935.

[0043] Examples of the functional group include a carboxylic acid group (including a carboxylic anhydride group), an ester group, an ether group, an aldehyde group, and a ketone group. A structural unit having a functional group can be introduced, for example, by subjecting an olefin polymer to a modification reaction.

[0044] The modified olefin polymer (E) according to the present invention preferably contains an olefin polymer modified with an unsaturated compound having at least one group selected from a carboxyl group and an acid anhydride group.

[0045] Specific examples of the unsaturated compound include unsaturated carboxylic acids or unsaturated dicarboxylic acids such as acrylic acid, methacrylic acid, α-ethylacrylic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, tetrahydrophthalic acid, methyltetrahydrophthalic acid, and endo-cis-bicyclo[2,2,1]hept-5-ene-2,3-dicarboxylic acid (Nadic acid (trademark)), as well as derivatives such as acid halides, amides, imides, acid anhydrides, and esters thereof. Among these, unsaturated dicarboxylic acids or acid anhydrides thereof are preferred, maleic acid, Nadic acid, and their acid anhydrides are more preferred, and maleic anhydride is particularly preferred. Maleic anhydride has a relatively high reactivity with olefin polymers before modification, is less likely to polymerize with maleic anhydride, and tends to be stable as a basic structure, and therefore has various advantages such as a stable quality of modified olefin polymers can be obtained.

[0046] Examples of the olefin skeleton portion of the modified olefin polymer (E) according to the present invention include ethylene polymers, propylene polymers, and 1-butene polymers. An example of a method for producing the modified olefin polymer (E) according to the present invention is a method in which an unmodified olefin polymer is graft-modified with a modifying agent (for example, an unsaturated carboxylic acid or a derivative thereof).

[0047] The graft modification of the olefin polymer can be carried out by a known method, for example, by dissolving the olefin polymer in an organic solvent, adding an unsaturated carboxylic acid or a derivative thereof, a radical initiator, and the like to the obtained solution, and reacting at a temperature of preferably 60 to 350°C, more preferably 80 to 190°C, for preferably 0.5 to 15 hours, more preferably 1 to 10 hours.

[0048] Examples of the organic solvent that dissolves the olefin polymer include aromatic hydrocarbon solvents such as benzene, toluene, and xylene, and aliphatic hydrocarbon solvents such as pentane, hexane, and heptane.

[0049] Another example of the graft modification method of an olefin polymer is a method in which an olefin polymer is reacted with a modifier (e.g., an unsaturated carboxylic acid and its derivative) using a radical initiator in the absence of a solvent in an extruder, etc. In this case, the reaction temperature is usually higher than the melting point of the olefin polymer, for example, 100 to 350° C., and the reaction time is usually 0.5 to 10 minutes.

[0050] Examples of the radical initiator include known radical initiators such as dicumyl peroxide, di-t-butyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne-3,2,5-dimethyl-2,5-di(t-butylperoxy)hexane, and 1,4-bis(t-butylperoxyisopropyl)benzene. The radical initiator is preferably used in a ratio of 0.001 to 1 part by mass relative to 100 parts by mass of the olefin polymer before modification.

[0051] <Olefin Polymer Composition> The olefin polymer composition of the present invention is a composition containing the ethylene polymer composition (A), the propylene polymer (B), the inorganic filler (C) and the fatty acid amide (D), and contains the ethylene polymer composition (A) in an amount of preferably 10 to 50 mass%, more preferably 20 to 45 mass%, and still more preferably 25 to 40 mass%, the propylene polymer (B) in an amount of preferably 30 to 70 mass%, more preferably 35 to 65 mass%, and still more preferably 40 to 60 mass%, the inorganic filler (C) in an amount of preferably 0.1 to 30 mass%, more preferably 1 to 30 mass%, and still more preferably 5 to 30 mass%, and the fatty acid amide (D) in an amount of preferably 0.1 to 15 mass%, more preferably 0.5 to 13 mass%, and still more preferably 1 to 12 mass%, based on 100 mass% of the olefin polymer composition.

[0052] The olefin polymer composition of the present invention has excellent sliding properties by containing the ethylene polymer composition (A) and the like in the above ranges. The olefin polymer composition of the present invention is excellent in strength because it contains the modified olefin polymer (E) in addition to the above components.

[0053] When the olefin polymer composition of the present invention contains the modified olefin polymer (E), the content is usually in the range of 0.1 to 5 mass %, preferably 0.5 to 4 mass % (the olefin polymer composition is taken as 100 mass %).

[0054] The olefin polymer composition of the present invention may contain other thermoplastic resins such as polyolefin resins, and additives for resins (for example, stabilizers such as heat stabilizers and weather stabilizers, crosslinking agents, crosslinking assistants, antistatic agents, slip agents, antiblocking agents, antifogging agents, lubricants, dyes, pigments, fillers, mineral oil-based softeners, petroleum resins, waxes, etc.) within the range not impairing the object of the present invention.

[0055] <<Method for producing olefin polymer composition>> The olefin polymer composition of the present invention can be produced by various known methods, for example, by melt-kneading and dry-blending the ethylene polymer composition (A), the propylene polymer (B), the inorganic filler (C), the fatty acid amide (D) and, if necessary, the modified olefin polymer (E).

[0056] <Molded body> The molded article of the present invention contains the olefin polymer composition of the present invention. The molding method for producing the molded article according to the present invention (molding method) specifically includes conventionally known molding methods for polyolefins, such as known thermoforming methods such as extrusion molding, injection molding, film molding, inflation molding, blow molding, extrusion blow molding, injection blow molding, press molding, vacuum molding, powder slush molding, calendar molding, and foam molding. The olefin polymer composition of the present invention is preferably processed by injection molding to obtain a molded article containing the olefin polymer composition of the present invention.

[0057] An injection molded article obtained by injection molding the olefin polymer composition of the present invention can simultaneously achieve high heat resistance (high deflection temperature under load (HDT)), high self-lubricity, and a low wear coefficient.

[0058] Specifically, the obtained injection molded article has a heat distortion temperature (ISO 75-1,2) of 140° C. or higher at 0.45 MPa and 120° C. or higher at 1.8 MPa, and a dynamic wear coefficient of 0.2 or lower.

[0059] The molded article of the present invention may be a molded article formed from the olefin polymer composition of the present invention, or may be a molded article having a portion, such as a surface layer, formed from the olefin polymer composition of the present invention.

[0060] Furthermore, the molded article made of the olefin polymer composition of the present invention is also excellent in mechanical properties. Specific examples of the molded article of the present invention include those used in a wide range of applications, from household goods such as daily necessities and recreational uses to general industrial and industrial products, such as home appliance material parts, communication device parts, electric parts, electronic parts, automobile parts, other vehicle parts, ship and aircraft materials, machine mechanism parts, building materials, civil engineering materials, agricultural materials, power tool parts, food containers, films, sheets, and fibers.

[0061] Furthermore, the molded product of the present invention can be widely used for conventionally known polyethylene applications, and since it has an excellent balance of properties such as abrasion resistance, self-lubrication, impact strength, and thin-wall moldability, it can be used for applications requiring these properties, such as gears, various bearings, cams, sliders, reels, cylinders, impellers, axial fans, rollers, bushes, various guide rails and rail guides, seat belt through anchors, various protective liner materials, metal coatings (laminations) such as steel pipes, electric wires, and automobile sliding door rails, various rubber coatings (laminations) such as pressure-resistant rubber hoses, automobile door gaskets, clean room door gaskets, automobile glass run channels, and automobile weather strips, and sliding materials such as linings for hoppers and chutes. EXAMPLES

[0062] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following description of the examples, "parts" refers to "parts by mass" unless otherwise specified. The ethylene polymer compositions (A) used in the examples and comparative examples are shown below.

[0063] (1) Ethylene-based polymer composition (A-1) Production of ethylene polymer composition (A-1) [Catalyst preparation] In a 10L reactor equipped with a stirrer that had been thoroughly purged with nitrogen, 4.0L of purified hexane and 95g of anhydrous magnesium chloride were added, and 350ml of ethanol was added dropwise at room temperature over 2 hours while stirring, followed by mixing at room temperature for about 1 hour. Next, 330ml of diethylaluminum chloride was added dropwise over 2 hours, and the mixture was mixed at room temperature for about 1 hour after the dropwise addition, followed by dropwise addition of 1.3L of titanium tetrachloride over 1 hour, and the reaction was carried out at 80°C for 1 hour.

[0064] After the reaction was completed, the solid portion was separated using a filter, and the solid portion was washed twice with purified hexane to obtain a solid titanium catalyst component. The titanium catalyst component had a titanium content of 6.8% by mass, a magnesium content of 15% by mass, and a chlorine content of 60% by mass. When the solid catalyst component was observed under an optical microscope at 390x magnification, it was observed to be an aggregate of multiple layers of fine solid particles of about 1 μm.

[0065] [Production of ethylene polymer composition (A-1)] After adding 12 L of purified n-decane to a 24 L autoclave that had been thoroughly purged with nitrogen, the temperature was raised to 50°C, and 12 mmol of triethylaluminum and 0.12 mmol of the above solid titanium catalyst component in terms of titanium atom were added at the same temperature. The catalyst charging port was then closed, and the internal pressure of the autoclave was reduced to 3.8 kg / cm. 2 Ethylene was introduced so that the pressure in the reactor became 0.1 kg / cm 2 , and the first-stage polymerization was carried out. The polymerization temperature was maintained at 45-46°C. 45 minutes after the introduction of ethylene, the pressure was quickly released, and when the pressure returned to normal, hydrogen was introduced at 5.0 kg / cm 2 . 2 G was introduced and ethylene was further increased to 3.00 kg / cm 2 The total pressure is 8kg / cm 2 The polymerization temperature was raised to 80°C and the second stage polymerization was carried out. The second stage polymerization time was 490 minutes. After the polymerization was completed, the temperature was lowered and a solid white polymer was separated and dried. The yield of the obtained ethylene polymer composition (A-1) was 3485 g, the intrinsic viscosity [η] was 5.73 dl / g and the density was 970 kg / m 3 It was.

[0066] On the other hand, the yield of ultra-high molecular weight polyethylene (ethylene homopolymer) [(a-1)-1] obtained by separately carrying out only the first stage polymerization under the same conditions was 595 g, and the intrinsic viscosity [η] was 28.0 dl / g. From this, the content of ultra-high molecular weight polyethylene [(a-1)-1] was estimated to be 17.1 mass%. From this, the intrinsic viscosity [η] of the low to high molecular weight polyethylene [(a-2)-1] produced in the second stage was calculated to be 1.15 dl / g using the following formula.

[0067] [η]all=[η]〔 (a-1)-1 ]×[(a-1)-1]mass%+[η][ (a-2)-1 〕×〔(a-2)-1〕mass% [η]all: intrinsic viscosity [η] (dl / g) of the entire polymer [ethylene polymer composition (A-1)] [η] (a-1)-1 〕: Intrinsic viscosity of (a-1)-1 [η] (dl / g) [(a-1)-1]: mass% [(a-1)-1] content (mass%) [η] (a-2)-1 〕: Intrinsic viscosity of (a-2)-1 (dl / g) [(a-2)-1] mass%: [(a-2)-1] content (mass%)

[0068] (2) Propylene-based polymer (B-1) Propylene homopolymer [Homo PP(b-1)-1] Prime Polymer Co., Ltd. "Product name: Prime Polypro J105G": MFR = 9.0g / 10min Propylene-α-olefin copolymer [random PP(b-2)-1] Prime Polymer Co., Ltd. "Product name: Prime Polypro F744NP": MFR = 7.0g / 10min

[0069] (3) Inorganic filler (C-1) Glass fiber chopped strand: Nippon Electric Glass Co., Ltd. "Product name: ESC 03 T480H"

[0070] (4) Fatty acid amide (D-1) Erucic acid monoamide: NOF Corp. product name "Alflow P-10"

[0071] (5) Modified olefin polymer (E-1) 100 parts by mass of propylene homopolymer (manufactured by Prime Polymer, trade name J106G: MFR = 15g / 10min), 4.0 parts by mass of maleic anhydride, and 0.35 parts by mass of organic peroxide (manufactured by Nippon Oil & Fats Co., Ltd., trade name Perhexyne-25B) were mixed in a Hexchel mixer, and the resulting mixture was melt-grafted and modified in a 100mmφ twin-screw extruder set at 270°C for a kneading time of about 1 minute and 30 seconds to obtain a modified polyolefin resin (E-1). The amount of maleic anhydride grafted in the resulting modified olefin polymer (E-1) was measured by IR analysis and found to be 3.0% by mass.

[0072] Various test pieces of the olefin polymer compositions obtained in the examples and comparative examples were prepared and their physical properties were measured by the following methods.

[0073] [Creating test pieces] Various test pieces were formed under the following conditions using an injection molding machine (J110-AD manufactured by Japan Steel Works, Ltd.). Cylinder temperature (℃): 50 / 220 / 230 / 230 / 230 / 230 / 230 Injection pressure (kg / cm 2 ):600 Screw rotation speed (rpm): 80 Mold temperature (℃): Water cooling (60℃)

[0074] [Thermal deformation test] In accordance with ISO75-1 and 2, the test specimen dimensions were 80 mm (length), 10 mm (width), and 4 mm (thickness), and the heat distortion temperature was determined at a standard deflection of 0.36 mm under loads of 0.45 MPa and 1.80 MPa and a heating rate of 120°C / h.

[0075] [Kinematic friction coefficient, specific wear rate] The dynamic friction coefficient and specific wear rate were measured using a Matsubara friction and wear tester in accordance with JIS K7218 "Sliding wear test method A for plastics." The test conditions were: mating material: S45C, speed: 50 cm / sec, distance: 3 km, load: 15 kg, and measurement environment temperature: 23°C.

[0076] [Examples 1 to 4 and Comparative Examples 1 to 3] The ethylene polymer composition (A-1), the propylene homopolymer [(b-1)-1], the propylene-α-olefin copolymer [(b-2)-1], the fatty acid amide (D-1) and the modified olefin polymer (E-1) were dry-blended in the amounts shown in Table 1 below, and fed into a twin-screw extruder (Toshiba Corporation, φ=26 mm, L / D=64, cylinder temperature: 230°C), and the inorganic filler (C-1) was side-fed into the vicinity of cylinder C11 and melt-kneaded to obtain an olefin polymer composition. Test pieces were prepared from the obtained olefin polymer composition, and the physical properties were measured by the methods described above.

[0077] The results are shown in Table 1.

[0078] [Table 1]

Claims

1. The present invention comprises an ethylene-based polymer composition (A), a propylene-based polymer (B), an inorganic filler (C) and a fatty acid amide (D), The ethylene polymer composition (A) comprises an ultra-high molecular weight ethylene polymer (component (a-1)) having an intrinsic viscosity [η] of 10 to 40 dl / g as measured in decalin solvent at 135° C., and a low- to high-molecular weight ethylene polymer (component (a-2)) having an intrinsic viscosity [η] of 0.1 to 5 dl / g as measured in decalin solvent at 135° C., wherein, with the total mass of components (a-1) and (a-2) being 100 mass%, component (a-1) is in the range of 15 to 75 mass% and component (a-2) is in the range of 85 to 25 mass%, and the composition has a density of 930 to 980 kg / m 3 and the intrinsic viscosity [η] measured in decalin solvent at 135° C. is in the range of 5 to 35 dl / g; the propylene polymer (B) is a composition of a propylene homopolymer (b-1) and a propylene / α-olefin copolymer (b-2); Further containing a modified olefin polymer (E), An olefin polymer composition.

2. The olefin polymer composition according to claim 1, wherein the content of the ethylene polymer composition (A) is in the range of 10 to 50 mass%, the content of the propylene polymer (B) is in the range of 30 to 70 mass%, and the content of the inorganic filler (C) is in the range of 0.1 to 30 mass% (wherein the olefin polymer composition is taken as 100 mass%).

3. The olefin polymer composition according to claim 1 or 2, wherein the content of the modified olefin polymer (E) is in the range of 0.1 to 5 mass % (wherein the olefin polymer composition is taken as 100 mass %).

4. The olefin polymer composition according to any one of claims 1 to 3, wherein the content of the fatty acid amide (D) is in the range of 0.1 to 15 mass% (wherein the olefin polymer composition is taken as 100 mass%).

5. The olefin polymer composition according to any one of claims 1 to 4, wherein the inorganic filler (C) is a glass fiber.

6. A molded article obtained by injection molding the olefin polymer composition according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Ram extruding machine for manufacturing plastic pipe

    JP1980028896A

  • Polyolefin resin composition for injection molding

    JP1989272646A

  • Laminate

    JP2001001450A

  • Polyolefin composition comprising propylene polymer and uhmwpe

    JP2001504895A

  • Resin composition and molding prepared with the resin composition

    JP2018123329A